Evidence Base Update of Psychosocial Treatments for Self-Injurious Thoughts and Behaviors in Youth. Issue 3 (4th May 2019) - Glenn, Catherine R.; Esposito, Erika C.; Porter, Andrew C.; Robinson, Devin J.
Abstract : The current review provides an evidence base update of psychosocial treatments for self-injurious thoughts and behaviors (SITBs) in youth. A systematic search was conducted of 2 major scientific databases (PsycInfo and PubMed) and ClinicalTrials.gov for relevant randomized controlled trials (RCTs) published prior to June 2018. The search identified 26 RCTs examining interventions for SITBs in youth: 17 were included in the 2015 review and 9 trials were new to this update. The biggest change since the prior review was the evaluation of Dialectical Behavior Therapy for adolescents (DBT-A) as the first Level 1: Well-established intervention for reducing deliberate self-harm (composite of nonsuicidal and suicidal self-injury) and suicide ideation in youth and Level 2: Probably efficacious for reducing nonsuicidal self-injury and suicide attempts. Five other interventions were rated as Level 2: Probably efficacious for reducing SITBs in youth, with the new addition of Integrated Family Therapy. This evidence base update indicates that there are a few promising treatments for reducing SITBs in youth. Efficacious interventions typically include a significant family or parent training component as well as skills training (e.g., emotion regulation skills). Aside from DBT-A, few treatments have been examined in more than one RCT. Given that replication by independent research groups is needed to evaluate an intervention as Well-established, future research should focus on replicating the five promising interventions currently evaluated as Probably efficacious . In addition, an important future direction is to develop brief efficacious interventions that may be scalable to reach large numbers of youth.